Environmental change, displacement, and pro-longed conflict: Climate Security in Singhere and Bissine, Casamance: Field Report - Sarzana, Carolina; Krendelsberger, Alexandra; Diallo, Ousmane; Ndiaye, Baye Mor Talla; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2022)
This report recounts historical information gathered through interviews and focus group discussions in Singhere and Bissine regarding displacement, resource use and production, climate and environmental problems, while also providing future outlook highlights. In addition, it provides recommendations on context-specific climate adaptation intervention needs.